If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + -10 + 3x + -4 = 0 Reorder the terms: -10 + -4 + -9x + 3x = 0 Combine like terms: -10 + -4 = -14 -14 + -9x + 3x = 0 Combine like terms: -9x + 3x = -6x -14 + -6x = 0 Solving -14 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -6x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -6x = 0 + 14 -6x = 0 + 14 Combine like terms: 0 + 14 = 14 -6x = 14 Divide each side by '-6'. x = -2.333333333 Simplifying x = -2.333333333
| 3*x+4=1 | | 21=60-12x | | a+(10-3)=30+10a | | 5-8*x=11 | | -56=-c-(-8) | | 4x+5=6.5 | | 3n^2+9n-12=0 | | 2(x+2)-5(2x+7)= | | 7x+2=-103 | | 2x+10-3=-2x+1 | | 10-2*x=4 | | -.75+j=-3.5 | | 4x+126=11x | | 19-2*x=4 | | 96=-24c | | -6a-5b-4= | | -3.75+j=-3.5 | | 96=-24 | | 4-3*x=34 | | 2x+7y+8= | | (v-3)(2v+1)= | | 6a-5b-4= | | 2-6*x=5 | | z^3-3z^2+(1+3i)z-6i+a=0 | | 2a^2-ab-15b^2=0 | | .5*x+1=11 | | c=15+40 | | 4x+10=x+37 | | -4+2t=1 | | 58=3a+10 | | 5-2*x=19 | | 8y+23=33 |